Distribution System Reconfiguration: Case Studies - Mahdavi, Meisam [UNESP]; Siano, Pierluigi; Alhelou, Hassan Haes; Guerrero, Josep M. (Wiley, 2021)
The distribution network is an important part of the power system infrastructure that links a high-voltage transmission system to end-users of electric energy. Three common methods to reduce the power loss of distribution systems are capacitor placement, distributed generation (DG) allocation, and distribution system reconfiguration (DSR). DSR can be classified into static and dynamic reconfigurations. In this chapter, first a mathematical modeling method of the conventional DSR problem, aiming at a loss minimization, is described. Then, results and solutions obtained by other researchers and literature in the field of network reconfiguration are presented. Also, all of the results and methods are compared with each other from the loss reduction amount, computational time, and voltage improvement point of view in order to show advantages and disadvantages of the proposed methods for distribution system reconfiguration.